Implemenstasi Prinsip-Prinsip UUD 1945 Dalam Sistem Ketatanegaraan - Rahma Mesa As Shawmi; Deko Rio Putra (Yayasan Darussalam Bengkulu, 2024)
The purpose of this study is to explain how the main values contained in the 1945 Constitution of the Republic of Indonesia are applied within the Indonesian constitutional framework. The focus of this study is how state institutions function to implement the principles of people's sovereignty, constitutional supremacy, authorization of power, and protection of human rights through their organization, authority, and interactions. This study uses a qualitative approach through literature review and document analysis. The purposively selected sample consists of relevant articles from the 1945 Constitution and Constitutional Court decisions that show how constitutional principles are applied in everyday life. However, the research population includes all laws and constitutional norms related to state administration. The results show that the application of the principles of the 1945 Constitution has resulted in the strengthening of state institutions and greater authority.